(untitled) (Journal of Pharmaceutical Negative Results, 2023)
‘In this modern globalized world, the social and cultural scenario has changed’ and the present-day world is one of stress and other of diseases. Now people usually seek medical helps be it allopathic, neuropathic, scientific or of any kind. The following paper supports the understatement that people could actually heal without any medical aid but by naturopathic means. Environment can increase or reduce our stress level which in turn impacts our bodies. Whatever we perceive with our senses puts an impact on our nervous, endocrine and immune system. Regardless of age or culture, humans have always found nature pleasing. In the modern world and patriarchal Society, women can be seen more victimized and thus more prone to depression, anxiety and other mental disorders. This paper will take into account the healing effect of Nature in bringing about a harmonal balance and order and in treating other mental disorders of women specifically by reducing their anxiety and depression. A woman is the steerer of a family, hence their health and mental well-being is an issue of great concern. And this can very well be taken care of if their association with Nature is assured.